(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article examines the image of the Antichrist in Dostoevsky’s work "The Brothers Karamazov". Also in this work of the author the image of brothers is embodied and the issue of love and help to each other is analyzed. The novel "The Brothers Karamazov" teaches us to be enlightened, to be spiritually open and pure, to believe in something great that helps us cope with life’s difficulties. who have moved into a pig.